The Effectiveness of the Duties and Functions of the Air and Water Police (Polairud) in the Rokan Hilir Police Station - Aprizal, R. Ardo; Sriono, Sriono; Toni, Toni (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
The Air and Water Police (Polairud Polri) is an integral part of the Indonesian National Police, tasked with providing protection, community services, and law enforcement. To support these duties, Polairud Polri must be perpetually prepared, both through human resources and key tools such as ships and aircraft. Polairud must anticipate threats and enhance operational capabilities, especially in water and air regions, to combat criminal acts in national and international waters. This study aims to analyze the effectiveness of the duties and functions of Polairud at Rokan Hilir Police Station, identify the obstacles faced, and provide recommendations to enhance Polairud's performance in the region. This research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews with Polairud members and document analysis related to Polairud's activities and operations in the Rokan Hilir region. The results indicate that Polairud's duties and functions at the Rokan Hilir Police Station are highly effective in addressing crime in the water area. However, several obstacles were identified, including unpredictable weather conditions, numerous undetected small ports and rivers, limitations in key supporting tools, personnel shortages, lack of maritime equipment and aircraft, and low legal awareness among the maritime community.  This study underscores the need for enhanced technology and key support tools for Polairud operations, increased personnel, and legal education for the maritime community. Enhanced synergy among stakeholders in the maritime sector is also essential to support comprehensive water area security.